2020
DOI: 10.1039/d0ra01594f
|View full text |Cite
|
Sign up to set email alerts
|

Dual stimuli-responsive lanthanide-based phosphors for an advanced full-color anti-counterfeiting system

Abstract: Dual stimuli-responsive lanthanide-based phosphors were prepared for constructing a multilevel full color anti-counterfeiting system, augmenting the security level for information protection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Rare-earth (RE) materials with unique electronic structures have become an indispensable resource in the world, which has been widely applied in next-generation solid-state lighting, solar cells, bio-images, luminescent films, security inks, anti-countering, optical thermometers, and so forth. [1][2][3][4][5][6][7] In the family of trivalent RE ions, samarium (Sm 3+ ) is a significant orange-reddish emitting activator owing to the emission transitions of 4 G 5/2 → 6 H J (J = 5/2, 7/2, 9/2, and 11/2). It has been confirmed that a strong absorption band was observed in the region of 350-450 nm as well.…”
Section: Introductionmentioning
confidence: 99%
“…Rare-earth (RE) materials with unique electronic structures have become an indispensable resource in the world, which has been widely applied in next-generation solid-state lighting, solar cells, bio-images, luminescent films, security inks, anti-countering, optical thermometers, and so forth. [1][2][3][4][5][6][7] In the family of trivalent RE ions, samarium (Sm 3+ ) is a significant orange-reddish emitting activator owing to the emission transitions of 4 G 5/2 → 6 H J (J = 5/2, 7/2, 9/2, and 11/2). It has been confirmed that a strong absorption band was observed in the region of 350-450 nm as well.…”
Section: Introductionmentioning
confidence: 99%
“…The current fluorescence assays usually require fluorescence spectrometer and specialized researchers, which is not suitable in on-site analysis [ 32 , 33 , 34 , 35 , 36 , 37 ]. In this research, a smartphone installed a Color Picker APP is used as a signal reader to detect the DPA by integrating with the as-prepared ratiometric fluorescent sensing, Figure 4 A.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis methods of DPA-Ce, DPA-Tb, DPA-Eu, and DPA-Ce-GMP follow our previous reports. , Briefly, Ce­(CH 3 COO) 3 ·6H 2 O and DPA were mixed and dissolved in 20 mL of EtOH and then exposed to UV radiation for 20 min to obtain DPA-Ce. DPA-Tb and DPA-Eu were feasibly obtained by mixing DPA with Tb­(NO 3 ) 3 ·6H 2 O or Eu­(NO 3 ) 3 ·6H 2 O, respectively, in 20 mL of EtOH.…”
Section: Methodsmentioning
confidence: 99%